Implementation of advance care planning amid the COVID‐19 crisis: A narrative review and synthesis. Issue 9 (27th July 2021) - Hirakawa, Yoshihisa; Saif‐Ur‐Rahman, KM; Aita, Kaoruko; Nishikawa, Mitsunori; Arai, Hidenori; Miura, Hisayuki
Abstract : Advance care planning is considered an important issue in end‐of‐life care for older adults. The ongoing COVID‐19 pandemic has interrupted the healthcare system and end‐of‐life care tremendously. This review aimed to explore available articles on advance care planning amid the pandemic and analyze qualitatively. PubMed and Google Scholar were searched on February 2021 using the relevant keywords. Retrieved articles were screened applying inclusion criteria. Any article describing advance care planning during the COVID‐19 era was included. A qualitative content analysis was conducted. In total, 20 articles incorporating 5542 participants from five countries were included. Among the articles, eight were primary studies and the rest were perspective papers or secondary analysis. From the qualitative content analysis six major themes emerged namely palliative care, lack of coordination among acute care, hospital palliative care, and long‐term care, community‐based advance care planning, real‐time dissemination of scientific information on the regional pandemic situation, online system and legislation. The COVID‐19 pandemic had decreased the uptake of advance care planning. Findings of the review suggested simplification of the procedure regarding advance care planning, implementation of community‐based advance care planning and utilization of online resources to enhance the process. Geriatr Gerontol Int 2021; 21: 779–787 .